Depresi pada Tokoh Kiriyama Rei dalam Anime Sangatsu no Raion - Sihombing, Gilbert Alexander B; Wiriani, Ni Made; Ari Sulatri, Ni Luh Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 1 (2024)DO - 10.24843/JS.2024.v06.i01.p05, 2024)
This research focuses on the depression of the character Kiriyama Rei in the anime Sangatsu no Raion. The purpose of the research is to analyze the symptoms, causal factors, and impact of depression on Kiriyama Rei. The theories used are literary psychology theory by Wellek and Warren and cognitive theory of depression by Beck and Alford. Informal and descriptive methods are used as research methods. The method of data collection is the method of observe and note taking. In the data analysis stage, the descriptive analysis method is applied and in the data analysis presentation stage, the informal method is applied. Based on the results of the analysis, the symptoms of depression experienced by Kiriyama Rei are affective group in the form of emotions of sadness, motivational group in the form of desire to escape and loss of motivation, negative group in the form of negative view of self, negative interpretation of experience, and critical view of the future, and physical and vegetative group in the form of sleep disorders. The causative factors of Kiriyama Rei depression are specific stres and non-specific stres. The effects of Kiriyama Rei depression are negative view of self, negative view of life experience, and negative view of the future. Kiriyama Rei was declared a depressed patient because she experienced more than five symptoms of depression in a few weeks